Legitimasi Ketertindasan melalui Narasi Agama di Media Sosial - Arwansyah, OK Dedy; Salam, Abdillah; Yusuf, Rum Ahmad (Universitas Medan Area, 2025)
This study examines the phenomenon of the legitimacy of oppression through religious narratives on social media, especially Instagram. Social media has become an influential space in disseminating religious content that is multi-interpretive, creating passive acceptance of existing socio-economic conditions. Using a qualitative approach and critical discourse analysis, this study analyzes how religious narratives spread through texts and visual elements function as hegemonic tools. The results of the study show that narratives such as